Behavior of one-way RC slabs flexurally strengthened with prestressed NSM CFRP laminates: assessment of influencing parameters - Hosseini, Mhoammadreza Mostakhdemin (2020)
The efficacy of the NSM technique using prestressed CFRP laminates for the flexural strengthening of RC slabs was assessed experimentally. The results obtained indicated that the application of NSM CFRP laminates with a certain level of prestress is a suitable strategy to increase the load-carrying capacity of slabs in terms of service limit state (SLS) conditions. The higher is the CFRP prestressed level the larger is the performance of the NSM technique in the improvement of the behavior of the slabs at SLS conditions, but the deflection at the maximum load of the slabs decreased with the increase of the prestress level. The prestressed NSM CFRP laminates were more effective in the slabs with the lower concrete strength class, mainly at SLS conditions. The increase of the percentage of the flexural reinforcement had a detrimental effect on the performance of prestressed NSM CFRP laminates. An analytical formulation was developed for predicting the cracking, yielding and maximum loads of RC slabs flexurally strengthened with prestressed NSM CFRP laminates and a very good predictive performance was obtained. An upper limit is proposed for the prestress level for ensuring a compromise of ductility and strengthening effectiveness of this type of structural elements.